Religiusitas dan Intensi Anti Korupsi: Peran Moderasi Kebersyukuran - Humaira Mumtazah; Agus Abdul Rahman; Sarbini Sarbini (Journal An-Nafs: Kajian Penelitian Psikologi, 2020)
Corruption is a behavior that cannot be socially or religiously justified. Interestingly, despite the corruption is prohibited in all religions in Indonesia, the index of corruption remains high as reported by the results of surveys of national and international institutions. Besides, research on this matter showed inconsistency in the relationships between religiosity and corrupt behavior. This research re-examined the relationship between religiosity and anti-corruption intentions and determined the moderating effect of gratitude as an intervening variable. Gratitude is one of the strongest religious values which is expected to reduce ones’ intention to do corruptions. The research was conducted using a correlational research design, involving 92 population in an educational foundation in Garut regency, West Java. Data were collected using the GRAT short form to measure gratitude and the Muslim Religiosity Scale (MRC) was employed to measure religiosity. Whereas, Anti-Corruption Intention Scale was used to measure the anti-corruption intention. The results of data analysis showed that religiosity and anti-corruption intentions were positively correlated (F= 154.1, p = .001, R2= .631), and gratitude moderated the increase in the relationship (R2= .668). Therefore, gratitude was regarded as an intervening variable that strengthened the correlation between religiosity and anti-corruption behavior by 3.7%.